2022
DOI: 10.1016/j.psj.2021.101593
|View full text |Cite
|
Sign up to set email alerts
|

TBHQ alleviates pyroptosis and necroptosis in chicken alveolar epithelial cells induced by fine particulate matter from broiler houses

Abstract: Fine particulate matter ( PM 2.5 ) from poultry houses has adverse effects on the health of animals and workers. Tert-butylhydroquinone ( TBHQ ), an antioxidant, is widely used in feed additives. The present study investigated the effects of TBHQ on broiler house PM 2.5 -induced damage in chicken primary alveolar epithelial cells ( AECII ) extracted from 16-day-old chicken embryos using the method of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…1 a). Different studies have shown that cellular exposure to PM 10 decreased concentration- and time-dependent cell viability 32 , 33 . However, this is not consistent with the results of our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…1 a). Different studies have shown that cellular exposure to PM 10 decreased concentration- and time-dependent cell viability 32 , 33 . However, this is not consistent with the results of our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the strong antioxidant activity of the CA. Indeed, Xi et al [10] found that TBHQ played an important role in attenuating PM2.5-induced pyroptosis and necroptosis in chicken primary alveolar epithelial cells by inhibiting the generation of reactive oxygen species (ROS). Liu et al [30] also found that TBHQ attenuates podocyte injury in diabetic nephropathy by inhibiting NADPH oxidase-derived ROS generation via the nuclear factor E2-related factor-2 /hemeoxygenase-1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant TBHQ is a highly effective antioxidant for feeds, and can prevent oxidative spoilage caused by air oxidation; protect fats, oils, fat-soluble ingredients and other natural components of feeds; and delay the adverse changes caused by the oxidation of foods [8,9]. Numerous studies have shown that the antioxidant TBHQ is essential as a feed preservative in the production of livestock and poultry feeds and can effectively protect feeds against oxidative deterioration [10,11]. In vivo, TBHQ can regulate the expression of antioxidant protein genes by activating proteins; it is often used in medicine as an activator of the nuclear transcription factor E2-related factor-2 [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LPS evidently increased the expression of immunofluorescent protein of NLRP3 in the IPEC‐J2 cells. Previous studies have demonstrated that TBHQ could alleviate pyroptosis induced by fine particulate matter in chicken alveolar epithelial cells and prevent neuroinflammation through inhibition of NLRP3 and its downstream proinflammatory factors in mouse (Bian et al, 2022; Xi et al, 2022). Interestingly, our results found that pretreatment with TBHQ effectively decreased the mRNA level and protein expression related to pyroptosis in LPS‐induced injury of IPEC‐J2 cells, moreover, it also decreased the expression of immunofluorescent protein of NLRP3 in LPS‐induced injury of IPEC‐J2 cells.…”
Section: Discussionmentioning
confidence: 99%